(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
1 - Se taluni istituti giuridici, quali l’aequitas e l’epicheia, son peculiarissimi del diritto canonico sino a indurre qualche studioso a escluderne ogni derivazione concettuale e financo ogni tangenza - per quanto ai più manifesta e acclarata - con gli analoghi istituti rinvenibili in ambito civilistico, viceversa il principio di legalità, “suapte natura”, appare essenziale a ogni ordinamento giuridico civile proprio di uno stato democratico o, meglio, proprio di ogni tipo di stato di diritto, principalmente quello di origine democratica. (segue) The Principle of Legality in the Canonical System and the Approach to Penal Law In this article, the Author examines the principle of legality and its expression in the canonical system and in canonical penal law in particular. Opening with a reflection on the origins of the principle of legality in its ecclesiological context of the Church as a community of the faithful, the article then treats the principle of legality in its relation to the three powers of governance - administrative, legislative, judicial - and an essential aspect inherent to the exercise of each, namely discretionality, rationality, and moral certitude, in light of canonical penal law. The article closes with a brief mention of the principle of episcopal collegiality in light of the principle of legality.